Biodegradation properties and thermogravimetric analysis of 3D braided flax PLA textile composites. Issue 1 (June 2022) - Kanakannavar, Sateeshkumar; Pitchaimani, Jeyaraj; Thalla, Arunkumar; Rajesh, M
Recent advances in the development and application of bio-based (natural fiber and biopolymer) composites are gaining broad attention because the resulting polymer completely degrades and does not release harmful substances. In this study, natural fiber 3 D braided yarn textile PLA (Polylactic acid) bio-composites are developed by film sequencing followed by hot-press compression molding. Bio-deterioration and thermal stability of the composites are analysed for storage, machining, transportation, and in-service uses in different environmental conditions (compost and thermal). Composite samples with different fiber wt.% (0, 22, 44) are exposed to compost soil. Tensile testing is performed under different configurations to characterise the tensile properties. Prepared bio-composite specimens are evaluated for weight loss and reduction in tensile properties over soil burial time, to observe the rate of biodegradation of braided yarn textile bio-composites. Fourier transform infrared (FTIR) and scanning electron microscopy (SEM) is employed to analyse the biodegradability of the composites. To study the thermal stability of the prepared bio-composites thermogravimetric (TG) analysis is carried out. Results showed that biodegradability, tensile properties and thermal stability of the composites are enhanced significantly with the reinforcement of 3 D braided yarn fabric.